Hydrodynamic modeling of a section of the river Purires at the height of the new hospital, in a possible climate change scenario - Borge-Leandro, David (2023)
The new hospital for the province of Cartago will be in the canton of El Guarco, with an estimated construction area of 9 hectares, on an area near the confluence of the Purires and Coris rivers. Historically in the area there have been problems related to overflowing rivers and floods. The morphometric parameters determined for the Purires river basin indicate that the basin is prone to flooding in the lower basin and the accumulation of sediments, this coupled with high slopes that decrease their degree of inclination as they approach the study point. For the realization of the project from which this article is derived, the use of an unmanned aerial vehicle and an RTK antenna was implemented, this to specify the altimetry of the area of interest, this activity results in a digital model of elevations with a resolution of 3.7 cm /pixel, main input for hydrodynamic modeling. The hydrodynamic behavior of a 1.5km section of the Purires river is evaluated, in Iber 2.4.3, from which the maximum spatial extension, its height of water and flow speed, as well as its residence time, are obtained, this for a possible Climate Change scenario. Results are obtained both in the area where the hospital will be built, the flood plains near the raised section of the river, as well as two bridges, bridge 6 of National Route 2, which connects the metropolitan area with the southern part of the country, and a cantonal bridge that communicates with the town of Barrancas.